2021
DOI: 10.3390/insects12090838
|View full text |Cite
|
Sign up to set email alerts
|

Life Table and Preference Choice of Frankliniella occidentalis (Thysanoptera: Thripidae) for Kidney Bean Plants Treated by Exogenous Calcium

Abstract: Exogenous calcium (Ca) has been used to induce host plant resistance in response to abiotic and biotic stresses, including from thrips attack. The aim of this study was to determine whether exogenously applied Ca affects the performance of Frankliniella occidentalis. We assessed the development time, total longevity, reproduction, and population parameters of F. occidentalis, and its preference choice on Ca-treated or untreated control kidney bean plants under laboratory conditions. The results showed that F. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…45 days). For instance, on average, a single female thrips can lay up to 60-80 eggs [23]. The eggs are deposited into plant tissues using the female's ovipositor.…”
Section: Life Cycle and Reproductive Behavior Of Wftmentioning
confidence: 99%
“…45 days). For instance, on average, a single female thrips can lay up to 60-80 eggs [23]. The eggs are deposited into plant tissues using the female's ovipositor.…”
Section: Life Cycle and Reproductive Behavior Of Wftmentioning
confidence: 99%
“…The results of the present study revealed that calcium treatment increased the repellent effect of HIPVs on F. occidentalis. Our previous study has also shown that the application of exogenous calcium to kidney bean plants reduces the selectivity of F. occidentalis [49]. However, the mechanisms involved remain unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that exogenous calcium supplementation significantly increases defense enzyme activity in kidney bean plants, as well as reducing the choice of F. occidentalis [12,49]. However, the effect of calcium treatment on the production of volatiles in kidney bean plants, and the potential effect on the indirect defense of F. occidentalis, remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This species is currently ranked among the most injurious thrips species because of the damage it causes via feeding, egg‐laying, and also transmission of plant viruses (He et al., 2020). At present, control of WFT is difficult due to its rapid evolution of resistance to a broad range of insecticides and its hidden lifestyle (Reitz et al., 2020; Zeng et al., 2021).…”
Section: Introductionmentioning
confidence: 99%